Associação da episiotomia e laceração perineal grave com disfunção do assoalho pélvico no pós-parto remoto - Lima, Clara Taína Silva (2018)
To evaluate the association between episiotomy and severe perineal laceration (third and fourth degreen) with the presence of urinary incontinence (UI), contractile function and ultrasonographic findings of the pelvic floor muscles (PFM) in the postpartum remote. Materials and Methods: Product 1 – A Systematic Review and Meta-Analysis of observational studies evaluating the association between perineal childbirth lesions and morphological alterations pf PFM evaluated by ultrasound was performed. Product 2 – cross-sectional observational study. It was performed with primiparous women from the Maternity School Assis Chateaubriand (MEAC), who were in the period from 12 to 36 months after term vaginal delivery. Women with urogenital tract infection, history of gynecological or rectal cancer, previous surgeries in the PFM, carriers of demyelinating diseases of the spinal cor dor who became pregnant again were excluded. The records of all women who had vaginal delivery between May and November 2015 were analyzed, and from this analysis, women who suffered severe perineal laceration and those who underwent episiotomy were identified. The women were selected to composse three groups: 1) women who underwent episiotomy (n=12); 2) women who suffered severe perineal laceration (n=9) and 3) women who maintained intact perineum (n=12). The initial evaluation consisted of a clinical and sociodemographic questionnaire, and the International Consulation on Incontinence Questionnaire – Short Form (ICIQ-SF). The physical evaluation was composed of Pelvic Organ Prolapse Quantification System (POP-Q) measurements, digital MAP palpation and perineometry. Statistical analyzes were performed using the Chi-square and U Mann-Whitney tests. Results: Product 1 – Both episiotomy and severe perineal laceration are associated with a greater likelihood of avulsion of the anus levator muscle (OR = 1,77, 95% CI 1,25-2,51) (OR = 4,31, 95% CI 2,34-7,91), respectively; defects of the sphincters (OR = 2,82, 95% CI 1,71-4,67) and increased urogenital hiatos área compared to women who did not experience these obstetric lesions. Product 2 – there was no relationship between the presence of UI and perineal traumas or muscle function (tone, pain, genital hiatos, perineal body, strength and resistance). However, it was possible to observe a statistical difference in muscle tone (p = 0.006) and perineal body size (p = 0.047) between groups. The presence of UI before (p = 0.021) and during (p = 0.025) gestation were related to the development of UI in the postpatum period. Conclusions: Episiotomy and severe perineal laceration are related to the presence of lesions in the MAP visualized by the US, but clinically we did not observe a relation with the presence of UI. Therefore, there is uncertainty regarding the changes seen by the US being decisive for having UI.